SIMBOL-SIMBOL TANGAN DI KOMUNITAS PELAYANAN MAHASISWA PANTEKOSTA (SUATU ANALISIS SEMIOTIK) - RUMENSER, CRISTIAN GILBERT; RATTU, JULTJE A.J.; WAROUW, MAYA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â  This research is entitled â€œSimbol-simbol tangan di komunitas Pelayanan Mahasiswa Pantekosta (Suatu analisis semiotika)â€. is focused on symbols that can be found in almost all aspects of human life. In this category, symbols are used on Pentecostal community. The aims of this research are to identify and classify kinds of symbol and to analyze and describe meaning of symbol that can be found in Pentecostal student community. The writer uses Pierce theory (1955) about sign and symbols in the process of identifying and classifying kinds of symbols and the process of analyzing and describing the meaning of symbols used in Pentecostal student services community. The data were collected in Sam Ratulangi University. The writer uses descriptive method to analyze the forms of symbols found in Pentecostal student services community activities in this research. The results of this research show that there are 13 symbols used in Pentecostal student services community. The writer clasissifies them into 2 parts; the first is general symbols, which consist of 2 symbols namely, Cross hand symbol, and greetings symbol. The second part is Komisariat symbols, which consist of 11 symbols, we are one symbol, two piece symbol, three symbol, bad odor symbol, Hand Money symbol, OK symbol, sevent symbol, hand strong symbol, Sarangaheo symbol, X symbol, K symbol. The meaning of the general symbols are to identity and as a union of all Pentecostal student services members. The meaning of the Komisariat symbols are to unity and togetherness.Â Keyword: Pentecostal student community, symbol, sign, descriptive Method